Heat-Resilient Greenery: Planting Strategies for Urban Medians in Bhubaneswar City, Odisha - Bhoi, Chandrasekhar (PT. Riset Press International, 2025)
Urban medians in rapidly growing cities like Bhubaneswar, Odisha, offer valuable yet underutilized opportunities for integrating climate-resilient green infrastructure. Despite facing harsh conditions—intense heat, compacted soils, limited root space, pollution, and water scarcity—these strips can serve as effective microclimate buffers. Given Bhubaneswar’s tropical climate and vulnerability to heatwaves, strategically selecting hardy, low-maintenance plant species is essential for transforming medians into functional, sustainable urban assets. This review analyzes the ecological and infrastructural conditions of Bhubaneswar’s urban medians, identifies essential plant traits for survival in high-stress environments, and recommends suitable native and adaptive species. It also highlights global and local case studies, proposes heat-mitigating design strategies, and explores options such as smart irrigation and modular planting. Emphasizing interdisciplinary collaboration, the review positions median planting as a vital component of Bhubaneswar’s climate resilience efforts and suggests pathways for future research and sustainable urban greening policies.